On the use of green plantations, winter gardens and greenhouses on the roofs of buildings and structures - Тkachenko Т.; Chebanov Т.; Chebanov, L.; Klimova І.; Pantyukhov О. (Ways to Improve Construction Efficiency, 2021)
The constant growth of the urban population has led to a number of serious social, economic and environmental problems. Due to the density of urban development, there is almost no space left for greenery, parks, squares. Not only urban recreational areas are being reduced, but also suburban green areas, which act as green urban belts. Such green belts are a source of oxygen, a zone of conservation of biodiversity of phyto- and zoocenoses, migration routes for biota from the urban environment to the natural and vice versa. In addition, they maintain the climate balance of the urban system, protecting it from wind, temperature changes, flooding, landslides and floods. Currently, the urban system spreads horizontally and vertically, which dramatically reduces the attractiveness of the landscape. The situation is complicated by economic reasons: the cost of land in the city center is very high. Therefore, it is more profitable to give it for construction, rather than creating recreation areas. Due to the lack of green areas in the central areas, there is an effect of "heat island" of urban centers, when the temperature difference between the central urban and suburban areas is about 4… 7 ° C. Factors that change the microclimate of urban coenoses also include: air pollution (change in its composition, which is expressed in an increase in the content of solid suspended particles and gaseous impurities); change in heat transfer due to the closed horizon, thermophysical properties of urban surfaces (heat capacity, reflectivity of impurities); artificial formation of heat flows during heating, operation of vehicles, at industrial enterprises. Economic and environmental problems of cities lead to social ones, when the level of chronic diseases increases, the psycho-emotional state of a person deteriorates, and the birth rate decreases. Therefore, modern cities need to use modern energy-efficient technologies on roofs - "green structures", conservatories and greenhouses, which are able to solve environmental, economic and social problems.